SETTLEMENT OF DISPUTES REGARDING OWNERSHIP RIGHTS TO LAND WITH MULTIPLE CERTIFICATES - RAFI SURYA PERMANA (Law Research Review Quarterly, 2025)
One of the problems often faced between the community and the government through the Agrarian and Spatial Planning/National Land Agency is the existence of duplicate certificates. Regarding the case of a double certificate dispute, it also occurred in the jurisdiction of the Agrarian and Spatial Planning/National Land Agency of Tegal City. This research uses a qualitative approach. The type of research in this legal research is empirical legal research. The data sources of this research use interviews and secondary data. The data collection technique for this research was carried out through conventional and online literature searches as well as interview methods. The data analysis technique used in this legal research uses qualitative data analysis techniques. The results of the research and discussion can be concluded as follows: Factors that can cause the emergence of dual land title certificates include several technical errors, due to overlapping in the issuance of land title certificates, and influenced by internal and external factors. The existence of dual land title certificates creates legal uncertainty in terms of land registration. Land title certificates should be strong proof of land ownership.; Settlement of disputes over ownership of dual-certified land in Tegal City by the Agrarian and Spatial Planning/National Land Agency of Tegal City is through mediation. In mediation, each party acknowledged ownership of 25 m2 of land.2and an agreement was reached that Brother Mohamad would pay for 25 m2 of land at a price of Rp. 45,000,000 to Mr. Tarjani. The Agrarian and Spatial Planning/National Land Agency of Tegal City has revised the Certificate of Ownership Number 4820/Kraton and Certificate of Ownership Number 269/Kraton so that there is no overlap. The issuance of the revised certificate of title is a form of state legal protection for the owner of the land certificate of title.